Kinetics and regulation of synthesis of the major polypeptides of thylakoid membranes in Chlamydomonas reinhardtii y-1 at elevated temperatures (The Rockefeller University Press, 1976)
Etiolated cells of Chlamydomonas reinhardtii y-1 exhibit rapid and linear initial kinetics of greening when exposed to light at 38 degrees C. The initial rate of chlorophyll accumulation under these conditions is greater than the maximal rate during greening at 25 degrees C. Synthesis of the major polypeptides of thylakoid membranes within intact cells was assayed during greening by the incorporation of [3H]leucine and the subsequent electrophoresis of total cellular protein on polyacrylamide gels in the presence of sodium dodecyl sulfate. At 38 degrees C the major membrane polypeptides (about 28,000 and 24,000 daltons in mass) were synthesized at a linear rate after exposure of the cells to light, with no evidence of a lag period. A 1-2 h preincubation in the dark at the higher temperature was necessary to achieve linear initial kinetics. Actinomycin D inhibited synthesis of the membrane polypeptides if added at the beginning of a 2 h dark preincubation, but not when added near the end. These results suggested that transcription of the messenger RNA for the membrane polypeptides occurred during the dark period at 38 degrees C. But the major membrane polypeptides were not made by y-1 cells in the dark. The wavelengths of light most effective in eliciting production of the membrane polypeptides were the same as those allowing chlorophyll synthesis. In contrast, wild type cells, which are capable of chlorophyll synthesis in the dark, also make the membrane polypeptides in the dark. The data indicate that at elevated temperatures synthesis of the major thylakoid membrane polypeptides is controlled at a posttranscriptional step, and that this reaction normally proceeds only under conditions which permit reduction of protochlorophyllide.